Potential of Activated Coal Fly Ash as an Adsorbent Material in Carbon Capture Technology - Putri, Rizki Aria; Syarif, Aida; Kalsum, Leila (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
The rising carbon dioxide (CO₂) emissions from biomass combustion processes have become a central concern in climate change mitigation. This study explores the utilization of coal fly ash as a cost-effective and environmentally friendly adsorbent in carbon capture technology. Thermal activation was applied to fly ash at temperatures of 600°C, 700°C, and 800°C to enhance its surface characteristics. Characterization using Iodine Number and X-ray Diffraction (XRD) revealed significant improvements in adsorptive properties, particularly at 600°C. The findings confirm that activated fly ash possesses high potential as a CO₂ adsorbent due to the presence of crystalline calcium oxide (CaO), which facilitates carbonate formation. This research supports the integration of waste-based adsorbents in sustainable CO₂ mitigation strategies.